Fortalecer la competitividad internacional y dimensiones sociales del desarrollo: correlaciones y contradicciones - Messner, Dirk (2002)
Globalization requires countries to strengthen and open their economies if they seek to connect successfully to the world economy, but what happens to the social dimension when countries try to achieve competitiveness? This article analyzes the articulations, disarticulations, and interactions that occur between competitiveness, the fight against poverty and social development. First, it explains how the relationships established between these three elements depend on the level of development achieved and, consequently, differ in the different regions. Next, the links and interdependencies between policies aimed at strengthening competitiveness and policies aimed at achieving social development are examined. Then, the concepts and previous approaches are illustrated with examples taken from the Latin American reality. The author ends up proposing four types of social policies, defined by the objectives or functions they fulfill.